An Excursion to Milam Glacier - Sinha, R. L. (Indian Forester, 1964)
The note is an illustrated itinerary of an excursion to Milam Glacier organised by the Botany Department of Lucknow University in 1938. The writer was one of the members of the party. It has further been supplemented by the writer during his subsequent tours of the tract. It describes briefly the route to Milam Glacier, the topography, the vegetation and fauna of the tract. A route map is also appended.